Diverging destinies in international perspective: Education, single motherhood, and child poverty - Juho Härkönen (Luxembourg Income Study (LIS), 2017)
Educational differences in family demography have gained wide attention, not least due to arguments that they amplify existing inequalities in child well-being and life chances. Despite the interest, there has been a lack of comprehensive cross-national descriptions of trends in educational differences in family demography, and just a few quantifications of their importance to social inequality. In this study, I used data from the Luxembourg Income Study (LIS) to describe trends in educational differences in single motherhood in 33 North American, European, and Asian countries, and to analyze whether these differences amplify differences in child poverty by maternal education. The prevalence of single motherhood has increased in almost all of the 33 countries. In many, educational differences in single motherhood have widened and single motherhood has increased particularly among the least educated. Educational differences in single motherhood can amplify differences in child poverty by maternal education, but only when both the educational gradient of single motherhood and the child poverty gap by single motherhood are large enough. These findings show that educational divergence in family demography is not limited to the United States, but that it is not a universal trend. Moreover, the study highlights the contingency of the inequality effects of these patterns and concludes that these effects can be countered by reducing the socioeconomic penalty of single motherhood.
Keywords: 330; education; single mothers; children; poverty